Beneficial microbiome and diet interplay in early-onset colorectal cancer - Zhou, Zhengyuan; Kleis, Linda; Depetris-Chauvin, Ana; Jaskulski, Stefanie; Damerell, Victoria; Michels, Karin B; Gigic, Biljana; Nöthlings, Ute; Panagiotou, Gianni (EMBO molecular medicine, 2025)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer and the second leading cause of cancer-related deaths worldwide. Although the risk of developing CRC increases with age, approximately 10% of newly diagnosed cases occur in individuals under the age of 50. Significant changes in dietary habits in young adults since industrialization create a favorable microenvironment for colorectal carcinogenesis. We aim here to shed light on the complex interplay between diet and gut microbiome in the pathogenesis and prevention of early-onset CRC (EO-CRC). We provide an overview of dietary risk factors associated with EO-CRC and contrast them with the general trends for CRC. We delve into gut bacteria, fungi, and phages with potential benefits against CRC and discuss the underlying molecular mechanisms. Furthermore, based on recent findings from human studies, we offer insights into how dietary modifications could potentially enhance gut microbiome composition to mitigate CRC risk. All together, we outline the current research landscape in this area and propose directions for future investigations that could pave the way for novel preventive and therapeutic strategies. In this review, G. Panagiotou and colleagues discuss the interplay between diet and gut microbiome in the pathogenesis and prevention of early-onset CRC (EO-CRC) and suggest directions for future research that could lead to new preventive and therapeutic approaches.